The Fall and Rise of Blasphemy Law - Herrenberg, Tom; Cliteur, Paul; Project Muse; Project Muse. (Baltimore, Maryland : Project Muse, 2016)
This collection centers around two trends that currently influence freedom of expression. The first trend confirms the fact that many Western countries have become, over a long period of time, less strict about sacrilegious expression. In the process, many repealed their blasphemy laws or became less harsh in their punishment of blasphemy, hence "the fall of blasphemy law." The second trend manifests an opposite movement, hence "the rise of blasphemy law". Over the last decades, namely, Western societies have witnessed multiple attempts to suppress speech that defames religion. To be sure, one particularly vicious way of re-energizing these interdicts against blasphemy has come from radical believers intent upon removing blasphemy from the public domain by violent means. With contributions by scholars from a wide range of disciplines, this volume seeks to offer an examination of topical issues relating to freedom of expression, censorship, and blasphemy in contemporary multicultural democracies.
Preface -- Foreword. Blasphemy : a victimless crime or a crime in search of a victim? / Flemming Rose -- 1. General introduction / Paul Cliteur & Tom Herrenberg -- 2. Blasphemy and the law : the fall and rise of a legal non sequitur / David Nash -- 3. The English law of blasphemy : the "melancholy, long, withdrawing roar" / Ivan Hare -- 4. On the life and times of the Dutch blasphemy law (1932-2014) / Paul Cliteur & Tom Herrenberg -- 5. Death of a princess / Paul Cliteur, Laetitia Houben & Michelle Slimmen -- 6. Rushdie's critics / Paul Cliteur & Tom herrenberg -- 7. John stuart mill's "if all mankind minus one" tested in a modern blasphemy case / Paul Cliteur, Tom Herrenberg & Bastiaan Rijpkema -- 8. Religious freedom and blasphemy law in a global context : the concept of religious defamation / Mirjam van Schaik -- 9. Blasphemy, multiculturalism and free speech in modern Britain / Rumy Hasan.
Issued as part of book collections on Project MUSE.
Includes bibliographical references (pages 235-251) and index.
Description based on print version record.
Keywords: Offenses against religion -- Western countries -- History; Blasphemy -- Western countries -- History; Electronic books